WAYS TO EFFECTIVELY USE FINANCIAL RESOURCES IN SOCIAL PROTECTION OF THE POPULATION (Conferencea, 2023)
This article explores ways to effectively use financial resources in the social protection of the population. The authors argue that financial resources are critical for supporting social protection programs, which are essential for promoting social welfare and reducing poverty. The article examines various strategies for improving the efficiency and effectiveness of financial resource allocation in social protection, including targeting resources to those in need, implementing social protection programs that are sustainable and effective, ensuring transparency and accountability in the use of financial resources, and promoting coordination among different stakeholders involved in social protection. The authors also highlight some of the challenges and limitations of implementing these strategies and provide recommendations for policymakers and practitioners seeking to enhance the impact of social protection programs. Overall, the article offers important insights into how financial resources can be effectively used to support social protection programs, which are crucial for promoting social welfare and reducing poverty.